Diagnóstico comunitario de salud de la ciudadela el chofer la banda sector III, septiembre – diciembre de 2013 - Díaz Chamba, Andrea Verónica (2013)
The present investigation has as main objective to Contribute the invigoration of the MODELO DE ATENCIÓN INTEGRAL DEL SISTEMA NACIONAL DE SALUD FAMILIAR COMUNITARIO E INTERCULTURAL in the Hospital Universitario de Motupe, contributing with statistical and data that will allow to the Basic Teams of Health - EAIS (Equipos de Atención Integral de Salud) to formulate local proposals of health, spread to improve the quality of life of the Ciudadela del Chofer La Banda Sector III. The universe was constituted by 184 families and 680 inhabitants, the present investigation is of descriptive type, in which facts and characteristic related with the population and its environment are detailed, the instrument for the gathering of information was the family record elaborated by MSP and an annex to this record, the interview form allowed to complete the information, it was also analyzed the data, obtaining results that they will serve as base line. Among the most relevant data include the most prevalent is the female sex, educational level outstanding is the top study and high school, also we found 3 illiterates, of which none is head of household, was identified 4 children with mild malnutrition, regarding school children and adolescents much of have good nutritional status and studies in regard to women with sexually active, the rhythm method is most often used for family planning. As for the epidemiological profile we highlight that the Hypertension is the chronic pathology that more prevails affecting to ages understood between the 20 and 64 years, among the degenerative illnesses we find the thyroid cancer, and what concerns to disabilities the most protruding is the physical disability. The investigation is supported with bibliography and annexes that it contemplates the development of the same one Keywords: Community diagnosis, Model of Integrated Health Care.